E-Learning For Elementary Arabic - Wan Arpah, Wan Ahmad (2001)

(untitled)
E-Learning is a process whereby learning can be done on line via the web using various tools as medium of learning. This will enhance the understanding capabilities and learning can be done anywhere at any time. This new trend will pave a new horizon in learning process and will redefine the role of students and teachers. It has a few distinct features that need some adaptation and adjustment to be done before one can enjoy the fruit of E-Learning. Looking at this perspective, E-Learning may become a very good alternative method in teaching. Teaching language especially the foreign one to tertiary students requires a lot of creativity from the teacher. Unless the program is designed properly, the subject would lose its appeal in a short time. This study is aimed towards producing a prototype web site to teach students of tertiary level a second language. Arabic was chosen because the language has been under-developed in the technological sense though the Malaysian society especially Muslim is enthusiastic to learn the language. The development of the system has been properly documented. A few problems in producing such web site has been noted. Further recommendation and related field of studies are also suggested to help further quests and researches. It is hoped that this study will spark new interest to develop this area especially to fit the Malaysian need.